The effect of cardiac rehabilitation on blood pressure, and on left atrial and ventricular functions in hypertensive patients - ÇİNÇİN, AHMET ALTUĞ; ÖZBEN SADIÇ, BESTE; YAĞCI, İLKER; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT; SAYAR, NURTEN (WILEY, 2021)
Purpose Hypertension is associated with left ventricular (LV) hypertrophy, impaired LV relaxation, and left atrial (LA) enlargement. Cardiac rehabilitation (CR) improves clinical outcomes in a broad spectrum of cardiac disease. The aim of our study was to determine the effect of CR on blood pressure (BP), and on LA and LV functions in hypertensive patients. Methods Thirty consecutive hypertensive patients who would undergo CR program, and 38 hypertensive patients who refused to undergo CR program were included. All patients underwent ambulatory BP monitoring and transthoracic echocardiography, which were repeated after completion of the CR program, or 12 weeks later in the control group. LA and LV functions were assessed by both speckle tracking and 3-dimensional echocardiography. N-terminal pro-brain natriuretic peptide (NT-proBNP) levels were assessed before and after CR. Results Although initial ambulatory BP values and NT-proBNP levels were similar between the groups, daily, day-time, and night-time BP and NT-proBNP were significantly lower in the CR group after rehabilitation. LA reservoir strain and LV global longitudinal strain of the CR group significantly increased after CR while no significant increase was observed in controls. Conclusion CR improves LA and LV strain while lowering BP and should be encouraged in routine management of hypertensive patients.
Keywords: cardiac rehabilitation; hypertension; left atrium; left ventricle; speckle tracking echocardiography; EUROPEAN ASSOCIATION; AMERICAN SOCIETY; EXERCISE REHABILITATION; MANAGEMENT; ECHOCARDIOGRAPHY; RECOMMENDATIONS; DYSSYNCHRONY; GUIDELINES; UPDATE; ADULTS